(untitled) (World Bulletin of Public Health, 2023)
As you know, unwanted incidents and complications in medicine, including anesthesiology and resuscitation, are not new. In the middle of the last century, the first works appeared in Russia and abroad demonstrating complications with various anesthetic treatments. According to the US Institute of Medicine, medical errors claim annually from 44 to 98 thousand lives of patients in American hospitals.